PERBEDAAN EFEKTIFITAS RUNNING HIGH INTENSITY INTERVAL TRAINING DIBANDINGKAN DENGAN JUMP ROPE EXERCISE TERHADAP PENURUNAN PERSENTASE LEMAK TUBUH PADA REMAJA DENGAN KATEGORI IMT OVERWEIGHT DI DENPASAR - Mohammad Kurniawan; Nila Wahyuni; uh Made Indah Sri Handari Adiputra (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT One of the many health problems experienced by teenagers and experiencing a significant increase in terms of numbers each year is Overweight and Obesity. Overweight and obesity conditions can be handled by increasingphysical activity in the form of running high intensity interval training and Jump rope exercise. The research wasrandomized pre and post control group design with sample of 15-18 year old teenagers amounted to 20 people anddivided into two groups namely group running high intensity interval training and Jump rope exercise. Samples that metinclusion and exclusion criteria were randomized and then measured fat percentage using Bioelectrical ImpendanceAnalysis (BIA). After 3 days of training a week for 4 weeks the sample is measured again for the data analysis. Theresult using Paired sample T-test to analyze that the group running high intensity interval training had p = 0,001 (p<0,05) and jump rope exercise had p = 0,003 (p <0,05) which mean in each group There was a significant decrease infat percentage during and before training. Then the two groups were tested using Independent sample T-test with p p =0,771 (p> 0,05), meaning there was no significant difference of effectivity in both groups. Key words: Adolescent, Overweight, Fat Percentage, Running High Intensity Interval Training, Jump Rope Exercise.